VARIABEL PENGETAHUAN DALAM PENELITIAN KESEHATAN MASYARAKAT - Mardhiati, Retno (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Researches in public health area often used composite variable. The composite variable used in public health researches includes health knowledge, attitude, intention, motivation, behavior, and many other more. The objective of this study is to provide an overview of data processing and analysis on composite variables in public health research. This study used a descriptive design method. Two scientific work assignments were used as the example of composite variable data processing which were selected using purposive sampling technique. Descriptive analysis was used to analyze data. The result shows that the composite variable consists of several items of question or statement. The creation of the knowledge composite variable started by determining the answer key of the question or statement item. The correct answer was then scored and totaled. Several studies continue to create categorical variables for knowledge composite variables. The categories can be sorted into 2 groups or more. The total score of knowledge composite variables can be grouped using mean or median value as the cut off point. Mean value can be used if the total knowledge score variable has a normal distribution, while median value is used if the distribution is not normal. The grouping of knowledge composite variables can also be done based on the value of Q1 (quartile 1) or Q3 (quartile 3). Finally, previous reference classification can be used to group the variable.